Crystal structure of N-(2-methylphenyl)ethoxycarbothioamide, C10H13NOS - Yeo Chien Ing; Tiekink Edward R.T. (Zeitschrift für Kristallographie - New Crystal Structures, 2018)
C10H13NOS, triclinic, P1̅ (no. 2), a = 7.2099(5) Å, b = 9.9751(6) Å, c = 15.0463(9) Å, α = 80.560(5)°, β = 81.827(5)°, γ = 73.887(6)°, V = 1020.19(12) Å3, Z = 4, Rgt(F) = 0.055, wRref(F2) = 0.186, T = 100 K.